2021
DOI: 10.3390/biom11111632
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis of Lytic Polysaccharide Monooxygenases Reveals the Pan-Families Occurrence of Intrinsically Disordered C-Terminal Extensions

Abstract: Lytic polysaccharide monooxygenases (LPMOs) are monocopper enzymes secreted by many organisms and viruses. LPMOs catalyze the oxidative cleavage of different types of polysaccharides and are today divided into eight families (AA9–11, AA13–17) within the Auxiliary Activity enzyme class of the CAZy database. LPMOs minimal architecture encompasses a catalytic domain, to which can be appended a carbohydrate-binding module. Intriguingly, we observed that some LPMO sequences also display a C-terminal extension of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 93 publications
1
35
0
Order By: Relevance
“…A number of these post-transitionally modified residues are also found in the AA10-GbpA2 domain interface of CbpD, likely encouraging a more elongated overall conformation, similar to the observed solution scattering conformation. Additionally, a recent bioinformatics analysis of 27 000 LPMOs found that most of the eight LPMO AA families are enriched in Ser and Thr residues in C-terminal regions that are prime candidates for PTM, specifically O-glycosylation (Tamburrini et al, 2021), which may affect secretion (Vorkapic et al, 2019). Of note, the Tma12 structure has an N-glycosylation at Asn158, structurally equivalent to Ser136 in CbpD, which has been identified as phosphorylated when CbpD is expressed and secreted by P. aeruginosa (Ouidir et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A number of these post-transitionally modified residues are also found in the AA10-GbpA2 domain interface of CbpD, likely encouraging a more elongated overall conformation, similar to the observed solution scattering conformation. Additionally, a recent bioinformatics analysis of 27 000 LPMOs found that most of the eight LPMO AA families are enriched in Ser and Thr residues in C-terminal regions that are prime candidates for PTM, specifically O-glycosylation (Tamburrini et al, 2021), which may affect secretion (Vorkapic et al, 2019). Of note, the Tma12 structure has an N-glycosylation at Asn158, structurally equivalent to Ser136 in CbpD, which has been identified as phosphorylated when CbpD is expressed and secreted by P. aeruginosa (Ouidir et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to cellulases which, as glycoside hydrolases (GHs), catalyze the breakage of 1,4-β-glycosidic bonds in cellulose via a hydrolytic mechanism, LPMOs follow an oxidative mechanism [2][3][4]. Extensive studies in LPMOs have led to their further classification as Auxiliary Activity (AA) enzymes in the Carbohydrate Active enZymes (CAZy; www.cazy.org; accessed on 20 November 2021) database [5], where they form eight separate families (AA9-AA11, AA13-AA17) [6,7]. LPMOs of fungal origin are found in the families AA9 (formerly GH61) and AA11.…”
Section: Introductionmentioning
confidence: 99%
“…A number of these post-transitionally modified residues are also in the AA10:GbpA2 domain interface of CbpD, likely encouraging a more elongated overall conformation, similar to the observed solution scattering conformation. Additionally, a recent bioinformatics analysis of 27,000 LPMOs found that most of the eight LPMO AA families are enriched for Ser and Thr residues in C-terminal regions that are prime candidates for PTM, specifically O - glycosylation (Tamburrini et al ., 2021), which may affect secretion (Vorkapic et al ., 2019). Of note, the Tma12 structure has an N-glycosylation at Asn158, structurally equivalent to Ser136 in CbpD, which has been identified as phosphorylated when CbpD is expressed and secreted by P. aeruginosa (Ouidir et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%